A Case Analysis on Enron; Ethics, Social Responsibility, and Ethical Accounting - Muhammad M. Rashid (New Innovations in Economics, Business and Management Vol. 1, 2021)
In 2001, just after the Asian crises of 1997-1998, the DotcomBubble, and 9/11, the Enron scandal sparked a Wall Street fraud crisis that shook the market to its core. Since then, scandals like Lehman Brothers and WorldCom in 2007-2008, as well as the Great Recession, have eclipsed it, although Enron remains one of the most significant incidents of accounting fraud. Despite the fact that the financial industry had become highly regulated by the early 2000s, deregulation of the energy industry permitted companies to speculate on future prices. Enron was hailed as a star inventor at the peak of dotcom bubble, but as the bubble burst, Enron’s plan to construct high-speed internet failed, and investors began to lose money. Furthermore, the operations’ financial losses were hidden by employing market to market accounting instead of book value, as well as special purpose organisations to hide debt. The main cause was determined to be a company with a toxic corporate culture that prioritised officer compensation rather than social responsibility, resulting in poor leadership. Is it possible then that; ethical accounting practices, social responsibility and ethics all become inferior goods as income rises in an ‘irrationally exuberant’era? This paper also further hypothesizes about the possibility of ethics, social responsibility and ethical accounting being inferior goods and points towards peaks in business cycles and financial crises as evidence.